Record of Discussions Forty Eighth Meeting National Development Council (19th February, 1999 Vigyan Bhavan, New Delhi) - Planning Commission (Planning Commission, 1999)
Shri K.C. Pant, Deputy Chairman, Planning Commission in welcoming the participants said that NDC as an august body represent the apex of a large and complex policy making structure that guides the course of development and economic progress of the country. He said that it was a forum to discuss the alternatives and arrive at a decision in a spirit of cooperation and mutual understanding.
Government of India, Planning Commission